Measuring the impact of loss ratios on the profitability of the Iraqi insurance company (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to provide a theoretical framework about loss, its importance and its repercussions on profitability in general insurance companies, highlight the role of loss in achieving justice for the target audience, prevent exploitation by the insurer in the issue of coverage provided to the insured, and address lack of trust in insurance companies by providing detailed information and periodicals regarding the activities Insurance companies, which will enhance their position in the hearts of the public. Show the results of applying the loss practically in two public companies practicing insurance activity. Financial indicators of profitability, debt, and trading ratios were used to reveal the extent of the impact of losses on the profitability of the Iraqi insurance company that was chosen as a sample for the research. 1. The researchers reached a set of conclusions, the most important of which was that the Iraqi General Insurance Company, from 2018-2022, did not achieve a significant loss at the level of its full activity and for all of its portfolios, and that claims and their coverage vary according to the compensation paid to the company’s indicates that its percentages vary from year to year during the research period insureds, and that the financial indicators related to its profitability and debt ratios The company's turnover.